This is a file in the archives of the Stanford Encyclopedia of Philosophy. |
Proof.
Since is a coarsening of
i for each i
N, K i(
(
) ).
Hence, K 1N (
(
) ),
and since by definition K i(
(
) ) = {
|
i(
)
(
) } =
(
),
K 1N ( (
) ) =
![]()
iN
K i( (
) ) =
(
)
Applying the recursive definition of mutual knowledge, for any m 1,
K mN ( (
) ) =
![]()
iN
K i ( K m - 1N ( (
) ) =
![]()
iN
K i( (
) ) =
(
)
so, since
(
)
, by definition we have
K *N (
(
) ).
Peter Vanderschraaf peterv@MAIL1.ANDREW.CMU.EDU |